Total Ankle Replacement Requiring Distal Tibiofibular Arthrodesis in a Dog - Burton, Neil J.; Krukowski, Maciej (VCOT Open, 2021)
This case report describes distal tibiofibular arthrodesis as a technique for achieving increased confluent bone support for the placement of oversized arthroplasty components for talocrural arthroplasty in an 18-month-old Labrador Retriever with talocrural osteoarthritis secondary to talar osteochondrosis. Computed tomography assessment for suitability for BioMedtrix canine ankle replacement surgery revealed the tibia to be undersized relative to the tibial component. Distal tibiofibular arthrodesis was performed to increase lateral bone support to permit placement of an otherwise oversized prosthesis. Subjective assessment of outcome with owner Liverpool Osteoarthritis in Dogs questionnaire to 6 months postoperatively as well as radiological assessment to 4 months postoperatively documented significant improvement in lameness in the operated limb with no complications. Distal tibiofibular arthrodesis is a means by which to achieve increased bone support prior to BioMedtrix canine total ankle replacement surgery. The surgical technique described herein permitted placement of an oversized talocrural prosthesis in this patient with good clinical function. This technique may permit use of this arthroplasty system in otherwise undersized patients until such a time that smaller implants are available from the manufacturer.
Keywords: tibiofibular arthrodesis; canine ankle replacement